Enhancing Arabic Reading Skills: A Prezi Program-Based Learning Material Development for Integrated Islamic Elementary Schools in Indonesia - Muchsinul Khuluq; Nurul Imamah (Journal of Arabic Language Learning and Teaching)
This study addresses the challenge of enhancing Arabic language learning through the development of engaging learning materials using Prezi software. Combining qualitative and quantitative approaches within the Research and Development (R&D) methodology, the study progresses through stages including needs identification, expert consultations, and model development. Implemented in a fifth-grade class, the model underwent testing using a pretest-posttest Control Group design, demonstrating significant improvements in students' reading comprehension (t0=4.6, exceeding critical t-value at 99% confidence level). Recommendations highlight the importance of Arabic language schools embracing technology, with tailored training for teachers and the utilization of programs like Breasy for material development. Emphasis is placed on optimizing learning media to foster student engagement, with implementation strategies focused on enhancing teacher proficiency and promoting active student participation in elementary Arabic language instruction.